Recessive progressive symmetric erythrokeratoderma results from a homozygous loss-of-function mutation of KRT83 and is allelic with dominant monilethrix. Issue 3 (13th December 2016) - Shah, Khadim; Ansar, Muhammad; Mughal, Zaib-un-Nisa; Khan, Falak Sher; Ahmad, Wasim; Ferrara, Tracey M; Spritz, Richard A
Abstract : Background: Progressive symmetric erythrokeratoderma (PSEK) is a rare skin disorder characterised by symmetrically distributed demarcated hyperkeratotic plaques, often with associated palmoplantar hyperkeratosis, with new plaques appearing over time. Most cases are inherited in an autosomal dominant manner, although a few cases exhibit apparent autosomal recessive inheritance. Objective: To identify the gene underlying autosomal recessive PSEK in a large Pakistani kindred. Methods: We first carried out autozygosity mapping using microsatellite markers in candidate regions of the genome. We then carried out exome sequencing of five family members, autozygosity mapping and mutation analysis using the exome data and verification by Sanger sequencing. Results: Autozygosity mapping and exome sequencing identified a homozygous frameshift deletion (c.811delA; p.Ser271fs) in KRT83, which co-segregated with the PSEK phenotype in the family and which is expected to abolish keratin 83, a type II keratin of hair and skin. Conclusions: At least some cases of PSEK result from loss-of-function mutations in KRT83 . Heterozygous missense substitutions in KRT83 have been implicated in autosomal dominant monilethrix, a rare hair disorder. Our findings indicate that at least some cases of autosomal recessive PSEK and autosomal dominant monilethrix are allelic, respectively resulting from loss-of-function and missense mutations in the KRT83 gene. Together, these findings indicate that different types of mutations in KRT83 can result in quite different skin and hair phenotypes.